RESPON PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Phaseolus radiatus L.) AKIBAT PENGGUNAAN PUPUK ORGANIK CAIR DAN PUPUK TSP - Wan Arfiani Barus; Hadriman Khair; Muhammad Anshar Siregar (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The aim of this study was to determine the growth and production responce of green bean by using of liquid organic fertilizer and TSP by randomized block design (RBD) factorial with two factors under studied namely : liquid organic fertilizer (B) which consist of four standrd that B0 = control, B1 = 5 cc / liter of water, B2 = 10 cc / liter of water and B3 = 15 cc / liter of water while fertilizer TSP (T) which consist of three standard that T0 = control, T1 = 15 g / plant, and T2 = 30 g / plants. Liquid organic fertilizer as first factor and fertilizer TSP as a second factor.